2001
DOI: 10.1046/j.1365-2265.2001.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

An audit of 500 subcutaneous glucagon stimulation tests to assess growth hormone and ACTH secretion in patients with hypothalamic–pituitary disease

Abstract: This large audit has shown that the glucose stimulation test is well tolerated and can easily be performed in an out-patient setting with minimal medical supervision. The 240 minute sample added little additional information and could be omitted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 33 publications
6
109
2
4
Order By: Relevance
“…Additionally, no correlation between BMI and age to peak GH responses were observed, peak GH responses occurred mainly between 120 and 180 minutes consistent with previous studies, 27,30 and that, overall, the GST was a well tolerated test. Nevertheless, these 21,22,28 and previous studies 20,23,24,31 did not specifically evaluate patients with glucose intolerance and frank diabetes and, for this reason, the characteristic of the GST and its reliability in testing for GHD in this population remains unclear.…”
Section: Historical Perspective Of the Use Of Glucagon Stimulation Tesupporting
confidence: 74%
See 2 more Smart Citations
“…Additionally, no correlation between BMI and age to peak GH responses were observed, peak GH responses occurred mainly between 120 and 180 minutes consistent with previous studies, 27,30 and that, overall, the GST was a well tolerated test. Nevertheless, these 21,22,28 and previous studies 20,23,24,31 did not specifically evaluate patients with glucose intolerance and frank diabetes and, for this reason, the characteristic of the GST and its reliability in testing for GHD in this population remains unclear.…”
Section: Historical Perspective Of the Use Of Glucagon Stimulation Tesupporting
confidence: 74%
“…25 The GST was initially described as a 4-hour test in older studies, 33 31 Accordingly, the authors proposed that the diagnostic utility of the simplified GST could be improved further by drawing an additional blood sample at 210 minutes when assessing GH deficiency. The audit by Leong et al 27 reported that the GST could be shortened by omitting the 240-minute blood sample. In this study of 414 patients, the majority of peak GH levels occurred between 120 and 180 minutes (85 %), and five patients had their peak GH levels recorded at 240 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our Endocrine Unit uses the GST as the first-line GH provocation test (16), which has been validated previously (25,26) and has been shown to be equivalent to the ITT (27,28). The Endocrine Society in its recent guidelines acknowledged the role of the GST for the diagnosis of GHD, particularly in the face of the recent shortage of GHRH (29) and in cases where the ITT may be contra-indicated (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…It is safe, with low cost, few contraindications, and an effective test to assess both GH and ACTH secretion (12). So far, few studies have evaluated GH response to GST.…”
Section: Introductionmentioning
confidence: 99%